Generalized Semicommutative and Skew Armendariz Ideals - Nikmehr, M. J. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We generalize the concepts of semicommutative, skew Armendariz, Abelian, reduced, and symmetric left ideals and study the relationships between these concepts.